Analysis Of Head Losses Consequent Section Diameter, Pipe Material and Flow Debit Using Contrast Test (Scheffe’s Method) at 900 Elbow Joint - Saut Kasdiardi Silalahi; Am. Mufarrih; Irwan Setyowidodo (IPTEK The Journal of Engineering, 2017)
Piping system is needed notice on group of high population people. Water flows come out from people residend sometimes unstable when used. This anomaly can be happened because factor of section diameter, pipe material, and flow debit passed through pipes elbow. This research intend to know effect section diameter, pipe material varians, flow debit of head losses and knowing coefficient losses consequent reynold number. This research is using factorial desain orthogonal array L12 then data analysis used Analysis Of Variance (ANOVA) with assistance minitab 16 software and contrast test (Scheffe’s Method). The results of this experiment head losses highest value of  pipe section diameter 1 inch towards ¾ inch, PVC (Poly Vinyl Cholide) pipe material, and flow debit 20 liter/minutes is 42.33 mm. For head loses lowest value of pipe section diameter ¾ inch toward 1 inch,  PE (Polyethylene) pipe material, and flow debit 10 liter/minutes is 5.33 mm, although highest coefficient losses of section diameter ¾ inch towards 1 inch, PVC (Poly Vinyl Cholide) pipe material, and flow debit 10 liter/minutes is 1.4602. ANOVA result and contrast test (Scheffe’s Method) concluded section diameter, pipe material, and fluid flow debit significant effect of head losses. Based the conclusion of research, reseacher suggest that small section diameter toward big section diameter, better pipe material and low flow debit  if want to reduce head losses value of piping system.